Ex Vivo Modeling of Malignant Pineal Tumors Using Viral Transformation of Transgenic Murine Pineal Gland Cultures. (16th November 2020) - Higgins, Dominique; Upadhyayula, Pavan S; Humala, Nelson; Mahajan, Aayushi; Mela, Angeliki; Sudhakar, Tejaswi; Zacharoulis, Stergios; Feldstein, Neil A; Canoll, Peter D; Bruce, Jeffrey N
Abstract: INTRODUCTION: Pineal tumors are rare entities, with pathology ranging from benign to highly malignant. The most common tumors in this region are germinomas, which are highly radiosensitive. However, other malignant tumors of this region, such glioblastoma, pineoblastomas and sarcomas are resistant to current therapies with a poor prognosis. Therapeutic advancements have been limited by the absence of tumor models and lack of readily available tissue specimen. METHODS: C57BL/6 mice with Trp53f/f; PTEN f/f floxed sites, and a stop-floxed YFP were used to harvest pineal glands by microdissection that were then dissociated and plated in SATO media. A PDGF-IRES-CRE virus was added to cells for Cre mediated deletion of p53 and PTEN, with expression of PDGF-B and YFP. Immunofluorescence and Western blotting were used to determine lineage expression patterns and to confirm expression of YFP, indicating viral infection with transformation. PCR was also used to confirm transgenic changes. Cell viability assays were performed using Cell Titer Glo bioluminescence. Orthotopic stereotactic injections were used for in vivo assays with serial MRIs to track tumor growth. RESULTS: Immunofluorescence of non-infected gland cells demonstrated a mixed population of cells including synaptophysin positive, indicating pineal parenchymal cells. 3 independent highly proliferative cell lines were generated from separate harvests, shown to be YFP positive and PCR demonstrated p53/PTEN loss confirming viral transformation. Western blots were negative for synaptophysin. Treatment with the pan-HDAC inhibitor, panobinostat, resulted in decreased cell viability indicating sensitivity to this chemotherapeutic agent. Orthotopic injections formed tumors in the pineal region that demonstrated heterogeneous staining with areas of GFAP, Nestin positivity and retention of YFP expression. CONCLUSION: Ex vivo transformation of transgenic mouse pineal glands is a robust method for the generation of malignant pineal tumors, with an in vivo tumor formation pattern similar to that of human tumors, and responsiveness to HDAC inhibitors. Further studies are warranted to characterize these tumors.